Features of constrained radial form turning - D. V. Moiseev; A. A. Ryzhkin (Advanced Engineering Research)
Introduction. The radial profile turning features are compared with the conventional turning by a straight tool with a fixed shear area. It is assumed to determine power characteristics in the cutting area by means of the calculated force dependences that take into account instantaneous shear areas and mean specific pressures available from experiments. Thus, the problem is solved in two stages. First, shear areas for various shaped profiles are determined, and then, experiments are performed to obtain mean specific pressures on the cut sites. This work objective is to solve problems of the first investigation stage: determining the instantaneous shear areas for different profiles of the shaped radial turning taking into account their dependence on the geometrics and time parameters of the radial penetration.Materials and Methods. Analytical dependencies are developed to solve the tasks. They make it possible to determine the instantaneous shear areas under radial turning of convex, concave and combined radius profiles in the course of cutting in. At this, cutting time, length of penetration, approach angle, and feed are taken into account. Shear areas and their increments can be determined through each full turn of the part. The analytical dependences obtained suggest features and variations in the magnitude of the instantaneous shear areas under radial shaping.Research Results. Instantaneous shear areas under the radial rotation of convex and concave radius profiles taking into account the geometrics and the increment time are calculated from the dependences obtained. This implies optimal conditions and modes of shape cutting.Discussion and Conclusions. Analytical dependencies and tabulated values of the shear areas are the background for determining power characteristics and energy costs on the basis of the specific pressures for shaped radial turning.